The ketogenic diet and metabolic treatments for neuropsychiatric disorders - Christopher M. Palmer (BJPsych Open)
The ketogenic diet, initially developed for epilepsy treatment, has gained attention as a potential intervention for neuropsychiatric disorders. A groundbreaking study by Campbell et al highlights its feasibility and potential efficacy in bipolar disorder, shedding light on shared mechanisms across neuropsychiatric disorders and the promise of metabolic treatment approaches.